Closed-loop cognition: the next frontier arrives. Issue 5 (May 2015) - Mishra, Jyoti; Gazzaley, Adam
<x xml:space="preserve">Abstract</x> A new study trains attention by implementing a closed-loop neurofeedback approach that monitors attention status in the whole brain using real-time fMRI. Offline analyses underscore information carried by the frontoparietal attention network as most relevant for the training-driven behavioral improvements.